THE INFLUENCE OF WORK ENVIRONMENT ON THE PERFORMANCE OF LECTURERS IN MASTERS AND DOCTORAL PROGRAMS IN MEDAN CITY - Lubis, Indah Sari Liza (Bussman Journal : Indonesian Journal of Business and Management, 2024)
Many factors cause a decline in an organization's employee performance. Whether internal factors or external factors. This study found that the work environment is considered one factor that influences the increase and decrease in lecturer performance. Therefore, this study will test whether the work environment influences the performance of lecturers in master's and doctoral programs in Medan City. Data collection using quantitative methods and data processing using PLS. Two hundred twenty-five professors from Medan City's private universities made up the research sample. The study's findings demonstrated that the work environment favorably and significantly impacted lecturer job satisfaction. Furthermore, the work environment had a slight but favorable influence on the performance of lecturers. Additionally, the work environment positively and substantially impacted performance through job happiness among instructors in Masters and Doctoral Programs at private universities in Medan City. Job satisfaction also had a favorable and significant effect on lecturer performance. It was determined that their work environment impacted lecturers' performance at Medan City's private universities